Generating Multibillion Chemical Space of Readily Accessible Screening Compounds - Grygorenko, Oleksandr O.; Radchenko, Dmytro S.; Dziuba, Igor; Chuprina, Alexander; Gubina, Kateryna E.; Moroz, Yurii S. (iScience, 2020)
An approach to the generation of ultra-large chemical libraries of readily accessible (“REAL”) compounds is described. The strategy is based on the use of two- or three-step three-component reaction sequences and available starting materials with pre-validated chemical reactivity. After the preliminary parallel experiments, the methods with at least ∼80% synthesis success rate (such as acylation – deprotection – acylation of monoprotected diamines or amide formation – click reaction with functionalized azides) can be selected and used to generate the target chemical space. It is shown that by using only on the two aforementioned reaction sequences, a nearly 29-billion compound library is easily obtained. According to the predicted physico-chemical descriptor values, the generated chemical space contains large fractions of both drug-like and “beyond rule-of-five” members, whereas the strictest lead-likeness criteria (the so-called Churcher's rules) are met by the lesser part, which still exceeds 22 million. [Display omitted] •A strategy for ultra-large readily accessible (REAL) compound libraries is described•Pre-validated two- or three-step three-component reaction sequences are used•A 29-billion chemical space with ∼80% synthesis success rate has been easily obtained Chemical Compound; Cheminformatics; Computational Chemistry by Subject